Regenerative Endodontic Management of an Immature Necrotic Premolar Using Advanced Platelet-Rich Fibrin - Sepideh Hosseini; Nazanin Chitsaz; Mohammad Hassan Hamrah; Donya Maleki; Emad Taghizadeh (Hindawi Limited, 2023)
Regenerative endodontic management is a feasible treatment for immature teeth with periapical radiolucency and necrotic pulp that simplifies continued root creation. Among the most prevalent health problems in an immature root is dental pulp necrosis, which is caused by caries, improper endodontic treatments, and trauma. Necrosis of the dental pulp can affect long-term tooth survival and preservation and serve as a source of bacteria infecting the periapical tissue and the maxillofacial space. Here, we report on the application of advanced platelet-rich fibrin plus (A-PRF+) therapy, as a regenerative endodontic treatment (RET), in a 12-year-old with necrotic pulp and asymptomatic apical periodontitis. Over a 24-month follow-up post-treatment, we observed resolving of symptoms and a complete root formation with considerable periapical healing.